Industrial training report: Aafiyat Holdings Sdn. Bhd. / Nur Munirah Mustapa - Mustapa, Nur Munirah (Universiti Teknologi MARA, Perlis, 2024)
This report provides an overview of my valuable 24-week internship at Aafiyat Holdings Sdn Bhd, conducted from March 1, 2024, to August 9, 2024. It focuses on the practical skills and knowledge I acquired, along with constructive feedback for the organization. I was placed in the Human Capital Department under the guidance of Cik Puan Nurul Ramlah, the Head of HR Operations. Throughout this period, I had the opportunity to immerse myself in various HR functions and processes, gaining hands-on experience that bridged the gap between theoretical knowledge and real-world application. Throughout the report, I have included my student’s profile and a detailed profile of the company. I have also reflected on my training, highlighting key learning moments and their impact on my professional development. Furthermore, I conducted a SWOT analysis to evaluate the strengths, weaknesses, opportunities, and threats related to the organization. Next, I also included the PESTEL analysis where it offers a broader perspective on the external factors influencing the company. Lastly, I also give recommendations regarding the weaknesses and threats of the company. In conclusion, this report summarizes my comprehensive learning journey, underscoring the importance of internships in shaping future professionals and contributing to organizational success.